2002
DOI: 10.1034/j.1399-302x.2002.170506.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the periodontal diseases: effects of catecholamines on the growth of periodontal bacteria in vitro

Abstract: Microorganisms possess the ability to recognize hormones within the host and utilize them to adapt to their surroundings. Noradrenaline and adrenaline, which are released during human stress responses, may act as environmental cues to alter the growth of individual organisms within subgingival biofilms. The aims of this study were to modify, for anaerobic culture, existing methodology used in determining microorganism catecholamine responses and to investigate the growth responses to noradrenaline and adrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 31 publications
1
124
0
Order By: Relevance
“…Another mechanism by which catecholamines can induce growth of Gram-negative bacteria, particularly enteric species involves induction of a novel growth stimulator (Lyte et al, 1996a;Freestone et al, 1999). Interestingly, this novel growth stimulator that we termed the noradrenalineinduced autoinducer (NA-AI; Lyte et al, 1996a;Freestone et al, 1999), induces its own synthesis and is heat stable, highly cross-species acting activity that stimulates increases Lyte and Ernst (1992); Lyte et al (1996, 1997a and 1997b); Freestone et al (1999, 2000, 2002, 2003, 2007a and 2007b Roberts et al (2002 and in growth of magnitude similar to that achievable with the catecholamines (Freestone et al, 1999). The NA-AI induces bacterial growth independently of Tf or Lf , and is also able to rapidly stimulate the recovery to active growth of viable, but non-culturable E. coli O157:H7 or Salmonella as well as increasing the rate of germination of Bacillus anthrax spores (Reissbrodt et al, 2002;Voigt et al, 2006).…”
Section: Microbial Endocrinologymentioning
confidence: 94%
See 1 more Smart Citation
“…Another mechanism by which catecholamines can induce growth of Gram-negative bacteria, particularly enteric species involves induction of a novel growth stimulator (Lyte et al, 1996a;Freestone et al, 1999). Interestingly, this novel growth stimulator that we termed the noradrenalineinduced autoinducer (NA-AI; Lyte et al, 1996a;Freestone et al, 1999), induces its own synthesis and is heat stable, highly cross-species acting activity that stimulates increases Lyte and Ernst (1992); Lyte et al (1996, 1997a and 1997b); Freestone et al (1999, 2000, 2002, 2003, 2007a and 2007b Roberts et al (2002 and in growth of magnitude similar to that achievable with the catecholamines (Freestone et al, 1999). The NA-AI induces bacterial growth independently of Tf or Lf , and is also able to rapidly stimulate the recovery to active growth of viable, but non-culturable E. coli O157:H7 or Salmonella as well as increasing the rate of germination of Bacillus anthrax spores (Reissbrodt et al, 2002;Voigt et al, 2006).…”
Section: Microbial Endocrinologymentioning
confidence: 94%
“…Insight into the growth induction mechanism may be provided by appreciating that the iron-binding catechol moiety found in siderophores such as enterobactin is also present in the catecholamine family of stress hormones (Freestone et al, 2000; Figure 1). Research from our laboratories and those of others have shown that NA, adrenaline and dopamine and certain of their metabolites (such as dihydroxymandelic acid and dihydroxyphenylglycol; Freestone et al, 2002 and all share the ability to stimulate growth in serum or blood growth by enabling bacteria to steal iron from normally inaccessible transferrin or lactoferrin (Freestone et al, 2000(Freestone et al, , 2007a(Freestone et al, , 2007b(Freestone et al, and 2008Roberts et al, 2002 andArmstrong, 2006 and. Iron is essential for growth of all bacterial pathogens, and its limitation in blood and mucosal secretions via its sequestration by transferrin and lactoferrin is one of the most important innate immune defences against infection (Ratledge and Dover, 2000).…”
Section: Microbial Endocrinologymentioning
confidence: 96%
“…Dopamine is produced in a subpopulation of non-sympathetic enteric neurons located within the intestinal wall [8]. Table 1 [ [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] shows the microbes responsive to catecholamine stress hormones. What is most apparent is that the spectrum of hormone responsive microbes is weighted towards bacteria inhabiting the gastrointestinal tract, particularly species such as Escherichia coli, Salmonella, Listeria, Campylobacter, and Yersinia [9, 12,13,[15][16][17][18]22].…”
Section: The Spectrum Of Stress Hormone Responsive Microbesmentioning
confidence: 99%
“…In an invitro study done by Roberts et al (2002) to determine whether noradrenaline and adrenaline which are released during human stress responses, signals to alter the growth of 43 microorganisms found within subgingival microbial complexes. 19 The researchers found that 20 species within the subgingival biofilm significantly grew from inoculation with noradrenaline and 27 species significantly grew when adrenaline was introduced. There was also a marked difference in the growth response within bacterial species and within and between microbial complexes.…”
Section: Stress and Microbiology Of Periodontal Diseasementioning
confidence: 99%